2013
DOI: 10.1007/s00394-013-0617-4
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of oat varieties in eliciting the early inflammatory events in celiac disease

Abstract: Purpose Celiac disease (CD) is an autoimmune enteropathy, triggered by dietary gluten. The only treatment is a strict gluten-free diet. Oats are included in the list of gluten-free ingredients by European Regulation, but the safety of oats in CD is still a matter of debate. The present study examined the capability of different oat cultivars of activating the gliadin-induced transglutaminase-2 (TG2)-dependent events in some in vitro models of CD. In addition, we compared this capability with the electrophoresi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 34 publications
1
45
0
1
Order By: Relevance
“…The reactivity of monoclonal antibodies against the main immunotoxic33mer peptide is proportional to the potential immunotoxicity of oat cultivars [43]. The most recent in vitro study further substantiates the diversity of oat cultivars [44]. The authors found significant differences among oat cultivars in eliciting the tTG2-mediated events of inflammation in patients with CD.…”
Section: A3 In-vitro Studiesmentioning
confidence: 82%
See 1 more Smart Citation
“…The reactivity of monoclonal antibodies against the main immunotoxic33mer peptide is proportional to the potential immunotoxicity of oat cultivars [43]. The most recent in vitro study further substantiates the diversity of oat cultivars [44]. The authors found significant differences among oat cultivars in eliciting the tTG2-mediated events of inflammation in patients with CD.…”
Section: A3 In-vitro Studiesmentioning
confidence: 82%
“…In a more recent in vitro study Silano et al [44] strengthened the idea of the variability of different oat cultivars in eliciting CD inflammatory events. They showed that Nave oat cultivars elicited early gliadindependent events, whereas Irina and Potenza varieties did not.…”
Section: The Toxic Peptides In Oatsmentioning
confidence: 97%
“…However, some pure oats cultivars have significant cross-reactivity with the most used monoclonal antibodies R5, G12 or Skerrit [58,[86][87]. Some celiac T-cell activating sequences from oat have been identified [11,[88][89] and some oat varieties have elicited early inflammatory events typical of CD [90]. Despite these evidences, it is still commonly believed that there is no reactivity in pure oats.…”
Section: Can Oats Contain Gluten?mentioning
confidence: 99%
“…Based on previous reports, oats have been used as a food resource and as a nutraceutical for treatment of cancer, diabetes, cardiovascular, and celiac diseases (15). The effectiveness of oats for treatment of celiac disease is attributed to anti-inflammatory effects (16).…”
Section: Introductionmentioning
confidence: 99%